New scoring system of an interview for the diagnosis of benign paroxysmal positional vertigo. (3rd March 2016) - Imai, Takao; Higashi-Shingai, Kayoko; Takimoto, Yasumitsu; Masumura, Chisako; Hattori, Kenji; Inohara, Hidenori
Abstract: Conclusion This study investigated a novel instrument to diagnose benign paroxysmal positional vertigo (BPPV). Objective To develop a new scoring system of an interview for the diagnosis of BPPV. Methods The answers to questions on dizziness and/or vertigo (D/V) (571 patients) were analyzed and the questions for which the answers differed significantly between the patients with and without BPPV were selected. Results This study established an intensive questionnaire with a scoring system. It consists of the following questions: (1) Is rotary vertigo a characteristic of your D/V? (2) Is your D/V triggered when you roll your head over in a supine position? (3) Does your D/V disappear within 5 min? (4) Have you previously experienced hearing loss in one ear, or have you experienced hearing loss, tinnitus, or ear fullness with this D/V? One point each was given to an answer of 'yes' to questions (1) and (2). Two points were given to an answer of 'yes' to question (3). One point was subtracted upon an answer of 'yes' to question (4). When the total score was greater than two points, the patient was diagnosed with BPPV. The sensitivity of the diagnosis of BPPV by this scoring system was 81% and the specificity was 69%.